Laparotomy for penetrating gastric trauma - A South African experience. Issue 5 (May 2022) - Allen, Natalie; Kong, Victor; Cheung, Cynthia; Rajaretnam, Nigel; Bruce, John; Laing, Grant; Manchev, Vasil; Xu, William; Clarke, Damian
Abstract: Introduction: Penetrating gastric injury (PGI) is common and although primary repair is sufficient for most injuries, several areas surrounding the peri-operative management remain contentious. This study reviews our experience in the management of PGI and review the clinical outcome at a major trauma centre in South Africa. Materials and methods: A retrospective study was conducted from January 2012 to April 2020 at a major trauma centre in South Africa. Results: 210 cases were included (184 male, median age: 30 years). Mechanism of injury was 59% stab wounds (SWs) and 41% gunshot wounds (GSWs). The AAST grade was predominantly (92%) grade 2 for all cases. 20% (41/210) were isolated gastric injuries. All cases underwent primary repair and there were no cases of suture line failure. Eleven cases (5%) had one or more injuries not identified at the index laparotomy: 7 were unidentified gastric injuries and the remaining 4 were unidentified non gastric injuries. There was no association between unidentified injuries and mechanism of injury or outcome. Fifty-seven (27%) cases experienced one or more complications. Eighty-two cases (39%) required intensive care unit admission. The overall median length of hospital stay was 7 (IQR 4-11) days. The overall mortality was 14%. GSW injuries were more likely to have additional organ injury, higher ISS and PATI scores, longer length of hospitalization, higher likelihood of ICU stay, greater morbidity and mortality than SW injuries. There was a slight increase in the wound sepsis rate as number of associated extra gastric injuries increased but this was not statistically significant. There was no difference in wound overall sepsis rate between SW and GSW injuries (2% vs 8%, p=0.121). Conclusions: Primary repair alone is sufficient for most PGI, but laparotomy is associated with high incidence of unidentified injury and surgeons must to be cognisant of the likelihood of these occult injuries.